2014
DOI: 10.1007/s00125-014-3186-z
|View full text |Cite
|
Sign up to set email alerts
|

Mortality after cancer among patients with diabetes mellitus: effect of diabetes duration and treatment

Abstract: Aims/hypothesis The prognostic role of different diabetes treatment types has not been studied in detail. We compared mortality rates among cancer patients with and without diabetes, accounting for diabetes treatment and diabetes duration. Methods This register-based study included all cancer patients diagnosed in Denmark during 1995-2009. The patients were classified into four groups according to diabetes status at the time of cancer diagnosis: no diabetes, diabetes without medication, diabetes with only oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 21 publications
3
75
0
5
Order By: Relevance
“…13.9 years for black females vs. 7.7 years for black males [7]. It has also been reported that cancer patients with diabetes experience higher mortality than cancer patients without diabetes [25] consistent with our findings. In this study, diabetes shortened the median survival age by 20 years among patients with pre-existing CVD, which was higher than that among patients without CVD even though hazard ratios for those with and without CVD were similar.…”
Section: Discussionsupporting
confidence: 93%
“…13.9 years for black females vs. 7.7 years for black males [7]. It has also been reported that cancer patients with diabetes experience higher mortality than cancer patients without diabetes [25] consistent with our findings. In this study, diabetes shortened the median survival age by 20 years among patients with pre-existing CVD, which was higher than that among patients without CVD even though hazard ratios for those with and without CVD were similar.…”
Section: Discussionsupporting
confidence: 93%
“…To the Editor: In the light of the general comments made about our article [1] by Holden et al [2], we acknowledge that we did not specify with sufficient emphasis that our study was based on the entire population of cancer patients in Denmark, that is to say, it was essentially demographic in its nature.…”
Section: Glp-1 Glucagon-like Peptidementioning
confidence: 94%
“…& The classification of patients is unequivocal: '…patients with diabetes but no history of glucose-lowering medication (DM NoMed; n=15,453), patients exclusively treated with oral hypoglycaemic agents (OHAs) (DM+OHA; n=17,708), or patients on insulin (DM+Ins; n=9,044)' [1]. The patients receiving glucagon-like peptide 1 (GLP-1) are included in the OHA group; however, the number of cancer patients treated with GLP-1 is negligible.…”
Section: Glp-1 Glucagon-like Peptidementioning
confidence: 99%
“…To the Editor: We read the article by Ranc and colleagues with interest [1]; however, we have concerns about its value. This large-scale study investigated the differences in survival following incident cancer in people with and without diabetes, accounting for diabetes treatment and diabetes duration.…”
Section: Oha Oral Hypoglycaemic Agentmentioning
confidence: 99%
“…
Abbreviation
OHA Oral hypoglycaemic agentTo the Editor: We read the article by Ranc and colleagues with interest [1]; however, we have concerns about its value. This large-scale study investigated the differences in survival following incident cancer in people with and without diabetes, accounting for diabetes treatment and diabetes duration.

Whilst the National Diabetes Register has the advantage of providing nationwide data for the whole of Denmark, the lack of information on specific diabetes treatments and diabetes type is a major limitation of this study.

…”
mentioning
confidence: 99%